Investigation of Current Digital Divide Between University Lecturers and Students in the English as a Foreign Language Context in North Bali - Artini, Ni Nyoman; Santosa, Made Hery; Suwastini, Ni Komang Arie (International Journal of Education, 2020)
Many experts argue that the digital divide has shifted from a gap in access to a gap in the skill to use information and communication technology (ICT). However, some people still have difficulties in getting access to ICT despite the advancement and increasing access and affordability of technology. Reflecting on this problem, this study aimed at finding out whether the digital divide between the lecturers and students of English as a Foreign Language existed and in what aspects the digital divide happened. This research was quantitative, with the data collected through an online survey involving 12 lecturers and 88 students in their third year. The findings revealed that both the gap in access and the gap in use existed between both groups. The result calls for the attention of the stakeholders and policymakers on the improvement of the quality of access to ICT as well as on the advancement in the use of technology, especially for the teachers so that they can keep up with the younger generation.